Pengumuman Layanan Publik - Winda Kustiawan; Melja Ramadhan; Lulu Ul Jannah; Inayah Sajida; Ainun Mardiah; Muhammad Ibnu Thariq; Siti Auliza (Lembaga Pengembangan Kinerja Dosen, 2024)
Public Service Announcements (PSA), commonly known as Public Service Advertisements (PSAs), are promotional strategies used in social marketing activities. Like commercial advertisements, the effectiveness of PSAs is crucial in changing target behaviors according to social marketing goals. Therefore, creative strategies in crafting persuasive messages and media placement are essential. Public service announcements serve as a medium for delivering social messages to the public, conveying information, and raising awareness about specific issues. This study employs a literature review method to understand relevant theories. Public service announcements play a significant role in increasing public awareness and are part of pragmatic discourse with illocutionary speech acts. The history of PSAs dates back to 1942 in the United States and has developed in Indonesia since 1968. Types of PSAs include corporate and political advertisements. PSA provide benefits such as raising awareness of social issues, providing education, fostering solidarity, and addressing existing problems. Examples of PSAs include reducing plastic usage, highlighting the dangers of smoking, environmental protection, corruption prevention, health protocol adherence, and drug abuse prevention.